Estudo perceptual da prosódia como elemento delimitador da estrutura de narrativas orais espontâneas: a diferença de tom - PEREIRA, Júlia Izabel Lopes (Universidade Federal do Pará, 2014)
The subject matter of this research is the perceptual study of prosody as a segmentation factor of spontaneous oral narratives and aims to confirm, or not, if the prosody helps the nonprofessional listener to recognize the structure of narrative texts. This study investigates whether the difference in intonation is an important prosodic element. This dissertation has a four-narrative corpus, the same corpus analyzed by Oliveira Jr. (2000), author of the project that inspired this research. To find out if the participants are able to understand the narrative structure under the perceptual point of view, we conducted a perception test with 112 volunteers, personally or electronically recruited at UFPA – Universidade Federal do Pará – and at UFAL – Universidade Federal de Alagoas. It was up to the participants to indicate the points of the narrative in which the speaker intended to finish a communication unit of the narrative. The interpretation of each communicative unit was subjective. Each story was presented in four different conditions, namely: (i) transcription without punctuation marks nor paragraphing, (ii) transcription accompanied by audio narration, (iii) audio narration alone and (iv) filtered audio narrative, resulting in an unintelligible speech, but keeping the prosodic structure of the discourse. In the first two conditions, the participants divided the transcribed text using crossbars (/). In the other two conditions, a computer program called ELAN was responsible for the segmentations. The data obtained were interpreted through conference tables, graphs, statistical analysis (Chi-Squared test) and acoustic analysis (operated by the PRAAT Program). The results indicate that prosody plays a fundamental role, helping nonprofessional listeners to comprehend the basic structure of a narrative discourse. Regarding the relevance of the differences in intonation, we may say that the Chi- Squared test found evidences that this segmentation factor works as suprasegmental element that assisted the participants in the comprehension of the narrative discourse structure. Thus, in this context, we are able ratify the vital role of prosody in the recognition of the structure of oral spontaneous narratives, as well as identify the relevance of the intonation in the participants perceptions.